Study of 3d Sloshing in a Vertical Cylindrical Tank - Cruchaga-Ssa., M (American Institute of Physics, 2018)
Moving liquid-gas interfaces appear frequently in both natural processes and engineering applications. In the case of partially filled tanks, for instance, the accurate description of the free surface transient behavior during transportation or earthquakes is of paramount importance for structural stability analyses. This work presents new experimental data of sloshing at laboratory scale in a vertical cylindrical tank with different filling levels, along with numerical simulations of selected cases using an open source finite volume application. Maximum and minimum experimental wave heights, measured with ultrasonic sensors, are reported for several non-resonant cases during the periodic steady state regime, along with snapshots of a video recorded near-resonance case. For the numerical simulations, a suitable mesh was designed based on a mesh convergence analysis focused on the simulated velocity profiles at the tank wall. A slight nonlinear behavior is detected in the experimental wave patterns, expressed as non-symmetrical minimum and maximum wave heights. The near-resonance case, in turn, shows a highly three-dimensional behavior of the free surface and a rotational effect. The numerical results obtained for the non-resonant cases show good overall agreement with the experiments, although the non-linear behavior is not accurately modelled. The evolution of the highly distorted free surface in the near-resonance case is well captured by the simulation, along with the observed rotational effect. © 2018 Author(s).